Sex work and modes of self-employment in the informal economy: diverse business practices and constraints to effective working. Issue 1 (30th September 2014) - Pitcher, Jane
Abstract : This article draws on research with adult sex workers in indoor settings in Great Britain to explore diverse forms of self-employment, employment relationships and small business development, set within the context of changes to the wider economy. It considers how external constraints such as the legal context, social stigma and dominant policy discourses can impact on sex workers' autonomy and actively work against their safety and wellbeing. The article argues that broad policy and legal approaches which fail to recognise the complexity of sex work constrain sex workers' opportunities for business development and improvement of their working circumstances. It suggests the need for recognition of sex work as legitimate labour, as a prerequisite for policy changes to support sex workers and pave the way for improved working conditions, not only in managed settings but also facilitating collective arrangements and independent lone working.